2022
DOI: 10.1371/journal.pone.0272368
|View full text |Cite
|
Sign up to set email alerts
|

General intelligence and executive functioning are overlapping but separable at genetic and molecular pathway levels: An analytical review of existing GWAS findings

Abstract: Understanding the genomic architecture and molecular mechanisms of cognitive functioning in healthy individuals is critical for developing tailored interventions to enhance cognitive functioning, as well as for identifying targets for treating impaired cognition. There has been substantial progress in uncovering the genetic composition of the general cognitive ability (g). However, there is an ongoing debate whether executive functioning (EF)–another key predictor of cognitive health and performance, is separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 97 publications
0
1
0
Order By: Relevance
“…A recent meta-analysis of studies on the relationships between the Wisconsin Card Sorting Test and intelligence found that overall shared variance was modest and just one third of the test variability could be accounted for by variability in common indicators of intelligence [31] . Studies on the genetic associations between executive functions and general intelligence suggest that they are overlapping but separable at genetic variant and molecular pathway levels, and that in adulthood, common EF abilities are distinct from intelligence that otherwise seems associated with working memory updating-specific EF abilities [ 32 , 33 ]. Overall, research has demonstrated that executive functions only partially correspond to the psychometric concept of intelligence, and their relationship is a controversial issue.…”
Section: Common Measures Of Intelligence In Studies On Neurocognitive...mentioning
confidence: 99%
“…A recent meta-analysis of studies on the relationships between the Wisconsin Card Sorting Test and intelligence found that overall shared variance was modest and just one third of the test variability could be accounted for by variability in common indicators of intelligence [31] . Studies on the genetic associations between executive functions and general intelligence suggest that they are overlapping but separable at genetic variant and molecular pathway levels, and that in adulthood, common EF abilities are distinct from intelligence that otherwise seems associated with working memory updating-specific EF abilities [ 32 , 33 ]. Overall, research has demonstrated that executive functions only partially correspond to the psychometric concept of intelligence, and their relationship is a controversial issue.…”
Section: Common Measures Of Intelligence In Studies On Neurocognitive...mentioning
confidence: 99%